2022
DOI: 10.2174/1566524021666210729144713
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin Mediated Degradation of EGFR by 17 β-estradiol in Triple Negative MDA-MB-231 (TNBC) Breast Cancer Cells Line

Abstract: Background: Triple Negative Breast Cancer (TNBC) commonly displays Epidermal growth factor receptor (EGFR). Effective EGFR degradation results in suppression of tumor in various models. Studies have addressed the relevance of this strategy in the treatment of TNBC. In the present study, we examined the effect of 17 β-estradiol on EGFR expression in MDA-MB-231 (TNBC) cell line and assessed whether 17 β-estradiol degrades EGFR by ubiquitination pathway. Objectives: To treat MDA-MB-231 cell lines with Cyclohexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Additionally, fluorescently labelled PEG-NEs were formulated as a negative control. The cell lines used to perform this experiment were MCF-7 and MDA-MB-231, as we have observed in previous works [ 36 , 37 ] and in our group that MDA-MB-231 expresses EGFR and MCF-7 expresses EpCAM. Additionally, to confirm this protein expression, we performed immunohistochemical analysis on both cell lines ( Figure 6 A).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, fluorescently labelled PEG-NEs were formulated as a negative control. The cell lines used to perform this experiment were MCF-7 and MDA-MB-231, as we have observed in previous works [ 36 , 37 ] and in our group that MDA-MB-231 expresses EGFR and MCF-7 expresses EpCAM. Additionally, to confirm this protein expression, we performed immunohistochemical analysis on both cell lines ( Figure 6 A).…”
Section: Resultsmentioning
confidence: 99%
“…Studies demonstrated that estrogens can exert functions by nonclassical ER mechanism. It has been reported that MDA‐MB‐231 cells can still be affected by estrogens even if ER is negative 45 . So far, the NK cell‐related mechanism for this abnormal low miR‐338‐3p level in BC cells is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that MDA-MB-231 cells can still be affected by estrogens even if ER is negative. 45 So far, the NK cellrelated mechanism for this abnormal low miR-338-3p level in BC cells is not clear. Therefore, we tend to explore the relationships of miRNA and BC.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible mechanisms that explain why estradiol benzoate and 17β-estradiol decrease HBx and inhibit HBV viral activity are also needed to be investigated. Estradiol may mediate its anti-HBV function through the Estrogen receptor-α (ER-α) signaling pathway as it does in HIV replication [ 22 ], or through activation of the E3 ubiquitination pathway by estradiol benzoate which may contribute to a decrease in HBV-related protein [ 23 ]. A distribution and a significant decrease in NTCP were observed in EB-induced cholestatic rats, as previously reported [ 24 ], which is the primary receptor of the HBV entrance of cells.…”
Section: Discussionmentioning
confidence: 99%